Potential impact of climate change on marine mammal biodiversity of Southeast Asia (A Review) - Dolar, Ma. Louella L.; Sabater, Edna R. (2011)
Climate change is affecting the oceans, and various studies have shown potential impacts on marine mammals. Impacts could be direct via habitat loss; or indirect through changes in the availability of prey, thus changing distribution and migration patterns and decreasing reproductive success of marine mammals. Further, increased water temperature could increase susceptibility to diseases and enhance impacts of other stressors. Species that have limited distributions and have little chance of expanding their range will be most vulnerable. Although most recent studies have focused on marine mammal species found in mid to high latitudes because of the relatively greater potential temperature changes in these areas, impacts on tropical species are also being recognized. |Most vulnerable are those who limited distributions, particularly the tropical riverine, estuarine and coastal species. Many of these species are found in Southeast Asia, a region that houses 32 of the 109-plus species of marine mammals. Among those with limited distribution that are already threatened are the Irrawaddy dolphin (Orcaella brevirostris); finless porpoise (Neophocaena phocaenoides); Indo-Pacific humpback dolphin (Sousa chinensis); and the dugong (Dugong dugon). These species have been classified as Vulnerable by the IUCN in its Red List, except S. chinensis, which is considered Near Threatened. Five sub-populations of the Irrawaddy dolphins, all found in southeast Asia, are Critically Endangered. Adding to these threats are high human population growth rates typical of the coastal areas in southeast Asia, increased dependence on the ocean as a source of food as the intensifying El Niño brings drought into inland areas, and lack of regulation or enforcement of fishery and conservation laws.
Keywords: Marine mammals -- Climatic factors; Climate change